Internet videoconferencing for patient–clinician consultations in long-term conditions: A review of reviews and applications in line with guidelines and recommendations. (April 2019) - Ignatowicz, Agnieszka; Atherton, Helen; Bernstein, Celia Janine; Bryce, Carol; Court, Rachel; Sturt, Jackie; Griffiths, Frances
Background: The use of internet videoconferencing in healthcare settings is widespread, reflecting the normalisation of this mode of communication in society and current healthcare policy. As the use of internet videoconferencing is growing, increasing numbers of reviews of literature are published. Methods: The authors conducted a review of the existing reviews of literature relating to the use of internet videoconferencing for consultations between healthcare professionals and patients with long-term conditions in their own home. The review was followed with an assessment of United Kingdom National Institute for Health and Clinical Excellence guidelines for patient care in the context of common long-term illnesses to examine where videoconferencing could be implemented in line with these recommendations. Results: The review of reviews found no formal evidence in favour of or against the use of internet videoconferencing. Patients were satisfied with the use of videoconferencing but there was limited evidence that it led to a change in health outcomes. Evidence of healthcare professional satisfaction when using this mode of communication with patients was limited. The review of guidelines suggested a number of opportunities for adoption and expansion of internet videoconferencing. Implementing videoconferencing in line with current evidence for patient care could offer support and provide information on using a communication channel that suits individual patient needs and circumstances. The evidence base for videoconferencing is growing, but there is still a lack of data relating to cost, ethics and safety. Conclusions: While the current evidence base for internet videoconferencing is equivocal, it is likely to change as more research is undertaken and evidence published. With more videoconferencing services added in more contexts, research needs to explore how internet videoconferencing can be implemented in ways that it is valued by patients and clinicians, and how it can fit within organisational and technical infrastructure of the healthcare services.